2021
DOI: 10.1109/tap.2020.3026910
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Angle Arrays by the NDF of the Radiation Integral

Abstract: Linear arrays have been well studied for their widespread applications. However, they suffer from severe limitations in their scanning capabilities due to the inherent main beam spreading. The combination of two linear arrays, radiating simultaneously, may provide the coverage of a wide angular domain by identical beams. More in general, first, we consider the radiation properties of a collection of continuous linear sources by following an inverse source approach which aims at investigating the spectral decom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…where θ ∈ [−π, π] is the observation variable, ‖ ′( )‖ is the differential element of , β = 2π/λ is the free space wavenumber and λ is the wavelength. As in [10], [14], the weight function ℎ(θ, ) is meant to add a directive behavior to each source element defined by the η parametric variable. In particular, if θ is the direction orthogonal to the η curve element, the function…”
Section: The Mathematical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…where θ ∈ [−π, π] is the observation variable, ‖ ′( )‖ is the differential element of , β = 2π/λ is the free space wavenumber and λ is the wavelength. As in [10], [14], the weight function ℎ(θ, ) is meant to add a directive behavior to each source element defined by the η parametric variable. In particular, if θ is the direction orthogonal to the η curve element, the function…”
Section: The Mathematical Backgroundmentioning
confidence: 99%
“…The two rectilinear sources support the electric currents 1 and 2 which give rise to the following field is the angle providing the direction orthogonal to each segment. In [10], it has been found that, when dealing with sets of non-overlapping rectilinear sources, an approximation of the NDF is given by the sum of the NDF due to a single rectilinear source. Hence, in this case,…”
Section: E Angle Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…In References [18][19][20], a different problem is considered, i.e., the inverse source problem when a (2D) source current must be reconstructed from its radiated field. Our investigation focused on estimating the NDF of the source according to its geometry so that a robust imaging algorithm can be set up.…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved by the SVD of the relevant radiation operator, analytically, when possible, by asymptotic upper bounds or numerically. For instance, circumference [18], angle [19], and conic [20] sources have been examined. In particular, in [19], theoretical arguments are developed for a collection of linear sources to show the role of their total electrical length to determine their NDF.…”
Section: Introductionmentioning
confidence: 99%